Materials for energy conversion devices - Sorrell, C. C.; Sugihara, Sunao; Nowotny, Janusz, 1936- (Woodhead Publishing in materials., 2005)
As the finite capacity and pollution problems of fossil fuels grow more pressing, new sources of more sustainable energy are being developed. Materials for energy conversion devices summarises the key research on new materials which can be used to generate clean and renewable energy or to help manage problems from existing energy sources. The book discusses the range of materials that can be used to harness and convert solar energy in particular, including the properties of oxide materials and their use in producing hydrogen fuel. It covers thermoelectric materials and devices for power generation, ionic conductors and new types of fuel cell. There are also chapters on the use of such materials in the immobilisation of nuclear waste and as electrochemical gas sensors for emission control. With its distinguished editors and international team of contributors, Materials for energy conversion devices is a standard reference for all those researching and developing a new generation of materials and technologies for our energy need. Detailed coverage of solar energy and thermoelectric conversionComprehensive survey of new developments in this exciting fieldEdited by leading experts in the field with contributions from an international team of authors.